Cognitive load and self-regulation: Attempts to build a bridge. (October 2017) - Boekaerts, Monique
Abstract: The editors of the Special Issue called for a more integrative approach to the study of cognitive load and self-regulation. The goal formulated for the Special Issue is ambitious. In my role as a constructive critic, I first summarized the findings in the 6 papers, identifying important questions and concerns that emerged while reading the papers. I also identified some general issues that need further clarification and elaboration: I argued that there is a strong need to reach consensus on the conceptualization and measurement of cognitive load and that new methodologies should be developed to capture cognitive load in real time and link it to strategy use. Highlights: A major challenge for research is to develop tools that can track shifts in perceived task demands. Another challenge is to describe the self-regulation processes that students use to counteract cognitive load. More differentiated models of cognitive load need to be developed. Joint research should be designed to connect the 2 research lines.